Respuesta :

Answer:

[tex] m=\frac{y_2 -y_1}{x_2 -x_1}[/tex]

And replacing we got:

[tex] m=\frac{1-(-3)}{3-(-3)}= \frac{4}{6}=\frac{2}{3}[/tex]

And we can use one of the points in order to find the intercept like this:

[tex] -3= \frac{2}{3} (-3) +b[/tex]

[tex] b =-3 +2=-1[/tex]

And the equation would be given by:

[tex] y= \frac{2}{3}x -1[/tex]

Step-by-step explanation:

We want an equation given by:

[tex] y=mx+b[/tex]

where m i the slope and b the intercept

We have the following two points given:

[tex] (x_1 = -3, y_1 =-3), (x_2=3, y_2 =1)[/tex]

We can find the slope with this formula:

[tex] m=\frac{y_2 -y_1}{x_2 -x_1}[/tex]

And replacing we got:

[tex] m=\frac{1-(-3)}{3-(-3)}= \frac{4}{6}=\frac{2}{3}[/tex]

And we can use one of the points in order to find the intercept like this:

[tex] -3= \frac{2}{3} (-3) +b[/tex]

[tex] b =-3 +2=-1[/tex]

And the equation would be given by:

[tex] y= \frac{2}{3}x -1[/tex]